2012
DOI: 10.1007/s00343-012-1228-2
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and tissue behavior of enrofloxacin and its metabolite ciprofloxacin in turbot Scophthalmus maximus at two water temperatures

Abstract: Turbot Scophthalmus maximus , an important aquaculture species in China, currently suffers from epizootic diseases because of high density aquaculture. Enrofl oxacin has been used to treat various systemic bacterial fi sh infections. However, studies concerning the pharmacokinetics of enrofl oxacin in turbot are limited. In this study, the pharmacokinetics of enrofl oxacin and its metabolite ciprofl oxacin, were investigated in the turbot following intravenous and oral administration at 10 mg enrofl oxacin/kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
38
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 35 publications
8
38
0
Order By: Relevance
“…Following PO administration, the T 1/2ka (0.13 hr) of ENR was shorter compared with 0.82 hr in snakehead fish (Fang et al., ), 1.394 hr in Korean catfish (Kim et al., ), 1.99 hr in turbot scophthalmus maximus (Liang et al., ) and 6.03 hr in seabass (Intorre et al., ); this indicated that ENR was rapidly absorbed in crucian carp after gavage. T 1/2β and AUC of ENR in crucian carp treated orally were 62.17 hr and 162.72 μg hr/ml, respectively; the values were considerably higher than those determined in Korean catfish (Kim et al., ), brown trout (Koc, Uney, Atamanalp, Tumer, & Kaban, ) and snakehead fish (Fang et al., ), while they were considerably lower than those of turbot scophthalmus maximus (Liang et al., ) and European eel (Fang, Yu, Cai, Zhou, & Huang, ). The reason for those differences is not clear.…”
Section: Pharmacokinetic Parameters Of Enrofloxacin and Ciprofloxacinmentioning
confidence: 99%
See 1 more Smart Citation
“…Following PO administration, the T 1/2ka (0.13 hr) of ENR was shorter compared with 0.82 hr in snakehead fish (Fang et al., ), 1.394 hr in Korean catfish (Kim et al., ), 1.99 hr in turbot scophthalmus maximus (Liang et al., ) and 6.03 hr in seabass (Intorre et al., ); this indicated that ENR was rapidly absorbed in crucian carp after gavage. T 1/2β and AUC of ENR in crucian carp treated orally were 62.17 hr and 162.72 μg hr/ml, respectively; the values were considerably higher than those determined in Korean catfish (Kim et al., ), brown trout (Koc, Uney, Atamanalp, Tumer, & Kaban, ) and snakehead fish (Fang et al., ), while they were considerably lower than those of turbot scophthalmus maximus (Liang et al., ) and European eel (Fang, Yu, Cai, Zhou, & Huang, ). The reason for those differences is not clear.…”
Section: Pharmacokinetic Parameters Of Enrofloxacin and Ciprofloxacinmentioning
confidence: 99%
“…China has given permission for ENR to be used in aquaculture, and it has become an essential strategy to confront and alleviate infectious disease and reduce animal mortality. The pharmacokinetics of ENR have been reported in a number of aquatic animals, including Korean catfish (Kim, Lim, Park, Hwang, & Yun, ), seabass (Intorre et al., ), snakehead fish (Fang, Zhou, & Liu, ), striped catfish (Phu et al., ) and turbot (Liang, Li, Zhao, Liu, & Chang, ). Nevertheless, information about the pharmacokinetics of ENR in crucian carp is deficient.…”
Section: Pharmacokinetic Parameters Of Enrofloxacin and Ciprofloxacinmentioning
confidence: 99%
“…The distribution half-lives of OTC in F. chinensis were 1.82 h in females and 2.50 h in males, both longer than those of antibacterial agents such as enroflxacin, florfenicol, sulfamethoxazole, marbofloxacin, and miloxacin (Liang et al, 2012;Rubio-Langre et al, 2012;Li et al, 2008) but shorter than sulphamonomethoxine in other species.…”
Section: Discussionmentioning
confidence: 96%
“…This is a well‐known conversion in most mammalian species, but appears to be species dependent in nonmammals. Teleosts such as the red pacu ( Colossoma brachypomum ), European seabass ( Dicentrarchus labrax ), turbot ( Scophthalmus maximus ), and Nile tilapia ( Oreochromis niloticus ) all convert enrofloxacin into ciprofloxacin, while the seabream ( Sparus aurata ) does not (Della Rocca, Di Salvo, Malvisi, & Sello, ; Intorre et al., ; Lewbart et al., ; Liang, Li, Zhao, Liu, & Chang, ; Xu, Zhu, Wang, Deng, & Zhang, ). Invertebrates such as the Chinese mitten‐handed crab, giant freshwater prawn, ridgetail white prawn, and Chinese shrimp ( Penaeus chinensis ) convert enrofloxacin into ciprofloxacin, while the European cuttlefish, Manila clam, and green sea urchin do not (Chang et al., ; Gore et al., ; Liang et al., ; Phillips et al., ; Poapolathep et al., ; Wu et al., ; Xu et al., ).…”
Section: Discussionmentioning
confidence: 99%